2008
DOI: 10.1142/s0192415x08006326
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Promotes Insulin-Like Growth Factors System in Ovariectomized Osteoporosis Rats

Abstract: Postmenopausal Osteoporosis (PMOP) is induced by the deficiency of estrogen in postmenopausal women. Electroacupuncture (EA) has been confirmed to be effective in clinic. We adopted ovariectomized osteoporosis model of rats to observe the role of EA in PMOP. Fifty female SD rats were divided randomly into 5 groups: intact (INT, n = 10), sham operation (Sham, n = 10), model (n = 10), estrogen (E, n = 10) and electroacupuncture (EA, n = 10). The bone mineral content (BMC) and the bone mineral density (BMD) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Acupuncture is an ancient Chinese method of healing. Previous studies have shown the efficiency of acupuncture on prevention of postmenopausal osteoporosis in humans [7] and in ovariectomized rats [8, 9]. Laser acupuncture (LA) is an noninvasive alternative too and has been proved equal biological effect as needle acupuncture [10].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is an ancient Chinese method of healing. Previous studies have shown the efficiency of acupuncture on prevention of postmenopausal osteoporosis in humans [7] and in ovariectomized rats [8, 9]. Laser acupuncture (LA) is an noninvasive alternative too and has been proved equal biological effect as needle acupuncture [10].…”
Section: Introductionmentioning
confidence: 99%
“…[23] Based on the model of growth control system, minor perturbations such as acupuncture around the singular points of the growth control system can be beneficial as disease modifying therapy in treating many inflammatory and degenerative disorders beyond symptom relief. Acupuncture has been shown to regulate bone morphogenetic protein, retinoic acid [84], wnt, nerve growth factor, [85,86] IGF-1 [87,87,88] , platelet derived growth factor [89], atrogin-1, protein kinase Akt1, [70] vascular endothelial growth factor, angiogenesis, [90] increase bone density [91,91,92], neuroplasticity (as in the healing of spinal cord injury) [87], and stem cell proliferation. [93] , [69] Acupuncture showed promise in ameliorating muscle atrophy, [70] osteoporosis [94] , [91] obesity [95], diabetes [96], polycystic ovary syndrome [86], stroke [90], and sepsis [97,98].…”
Section: The Singularity and The Utility Of The Organizer Networkmentioning
confidence: 99%
“…4,17,18 For example, BL 23 is an acupoint on the BL, located inferior and lateral to the spinous process of the second lumbar spine, used frequently in the management of menopausal hot flashes and osteoporosis. 4,17,18,33,34 Acupuncture at BL 23 has been shown to be effective in promoting bone formation, improving bone architecture, and reversing osteoporosis in the mice model. 33,34 These effects were suggested in relation to some degree of enhancement in the secretion of sex hormone and declining bone turnover by decreased OC levels.…”
Section: Chien Et Almentioning
confidence: 99%
“…4,17,18,33,34 Acupuncture at BL 23 has been shown to be effective in promoting bone formation, improving bone architecture, and reversing osteoporosis in the mice model. 33,34 These effects were suggested in relation to some degree of enhancement in the secretion of sex hormone and declining bone turnover by decreased OC levels. 33,34 There has been no report Change from baseline was defined as (score at 10th week -baseline score)/baseline score.…”
Section: Chien Et Almentioning
confidence: 99%
See 1 more Smart Citation